Radioactivity in the Marine Environment: Cosmogenic and Anthropogenic Radionuclides. Issue 1 (27th December 2018) - Benitez‐Nelson, Claudia R.; Buesseler, Ken; Dai, Minhan; Aoyama, Michio; Casacuberta, Núria; Charmasson, Sabine; Godoy, José Marcus; Johnson, Andy; Maderich, Vladimir; Masqué, Pere; Moore, Willard; Morris, Paul J.; et al.
Abstract : Natural and anthropogenic radionuclides are used to study a suite of environmental processes. Yet their applications in aquatic systems are hindered by a general lack of knowledge regarding the underlying concepts of radioactivity, the occurrence of radionuclides in ecosystems, and the equations used to describe their decay mechanisms in environmentally applicable ways. The goal of this lecture is to provide upper level undergraduate and graduate students with a basic understanding of how cosmogenic and anthropogenically produced radionuclides can be used to address a range of environmentally relevant questions in marine systems. The lecture begins with a brief introduction to cosmogenic and anthropogenic radionuclide production and sources to the marine environment. The remaining lecture focuses on specific case studies using these radionuclides in a range of applications including: ocean circulation and mixing, particle scavenging, and sedimentation/age dating. This lecture is the third of a four‐part lecture series on radionuclides in the marine environment.